Community Learning Activities in Reducing Functional and Qur'anic Illiteracy in Belencong Hamlet - Sri Damayanti; Muhammad mahfuz; Muazzam Khairi; Dian Aulia; Wawan Wiyandi; Yuniati Yuniati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This community service activity aimed to strengthen community-based learning in reducing functional illiteracy and Qur'anic illiteracy in Belencong Hamlet, Gunung Sari District, West Lombok Regency. The urgency of the program is supported by regional education statistics showing that in 2024 the illiteracy rate among residents aged 15 years and over in Lombok Barat reached 15.35%, higher than the Nusa Tenggara Barat provincial rate of 10.17% (BPS Provinsi Nusa Tenggara Barat, 2025). The activity was implemented through observation, socialization, training, and mentoring in collaboration with the Community Learning Activity Center. The target groups consisted of adult residents aged over 50 years with low basic literacy skills and children under 8 years old who required Qur'anic literacy assistance. The adult literacy activity was conducted twice a week, while Qur'anic literacy mentoring was conducted Monday to Thursday from 15.00 to 16.30 WITA. The success indicators included the ability to recognize letters, read simple words and sentences, write simple sentences, perform basic arithmetic, recognize hijaiyah letters, pronounce letters correctly, and read Iqro' according to level. Quantitative documentation of pre-activity and post-activity results is presented in the results section and should be completed with the authors' field data before submission. The strengthened manuscript shows that the activity not only increased enthusiasm but also provided a measurable framework for evaluating literacy improvement, character formation, and learning discipline.